MENINGKATKAN MOTIVASI BELAJAR SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN COMPLETE SENTENCE PADA MATA PELAJARAN BAHASA INDONESIA DI KELAS V SD/MIS MADRISATUL IKBAR TEMBUNG - Nurmayani Nurmayani; Dewi Pratiwi; Sorta Simanjuntak (Universitas Negeri Medan, 2020)
This type of research is Classroom Action Research (CAR), which aims to find out the increase in student motivation in using the complete sentence learning model in Indonesian subjects writing essays in class V SD / MIS Madrisatul Ikbar Tembung. Based on data analysis, that the results of Cycle I Meeting I there were 5 students who were motivated with a percentage of 16.67% and 25 students were not motivated with a percentage of 83.33%, and at Meeting II there were 7 students who were motivated with a percentage of 23, 33% and 23 students were not motivated with a percentage of 76.67%. In Cycle II Meeting I there were 18 students who were motivated with a percentage of 60% and 12 students were not motivated with a percentage of 40%, and at Meeting II there were 29 students who were motivated with a percentage of students 96.67% and 1 student not motivated by the percentage of students is 3.33%. Research data from the students' learning motivation questionnaire also increased, namely in the initial condition before the action there was 1 student who experienced high motivation with a percentage of 3.33% while in the final condition there were 24 students who had high motivation with a percentage of 80%. Then it can be concluded that by using the Complete Sentence learning model can increase student motivation in Indonesian subject matter writing essays in class V SD / MIS Madrisatul Ikbar Tembung of Academic Year 2019/2020.Keywords : Complete Sentence, motivation to learn, Indonesian Language